"y^2\/2+2ye^t+(y+e^t)y'=0"
Multiply by 2
"y^2+4ye^t+2(y+e^t)y'=0"
"y^2+2ye^t+e^{2t}+2(y+e^t)y'+2ye^t+2e^{2t}-3e^{2t}=0"
"(y+e^t)^2+2(y+e^t)y'+2(y+e^t)e^t-3e^{2t}=0"
"(y+e^t)^2+2(y+e^t)(y'+e^t)=3e^{2t}"
Notice that
"((y+e^t)^2)'=2(y+e^t)(y'+e^t)"
Let "z=(y+e^t)^2"
then
"z+z'=3e^{2t}"
Using an integrating factor
"u(t)=e^{\\int1dt}=e^t"
General solution is
"z=\\frac{\\intop e^t3e^{2t}dt+C}{e^t}=\\frac{e^{3t}+C}{e^t}"
"(y+e^t)^2=\\frac{e^{3t}+C}{e^t}"
"y+e^t=\\pm \\sqrt{\\frac{e^{3t}+C}{e^t}}"
"y=\\pm \\sqrt{\\frac{e^{3t}+C}{e^t}}-e^t"
Answer: "y=\\pm \\sqrt{\\frac{e^{3t}+C}{e^t}}-e^t"
Comments
Leave a comment